The Effect of the Tourism Sector on Regency and City Gross Regional Domestic Product in Central Java Province - Zahrotun Nisa, Aulia; Khoirudin, Rifki (BALANCE: Economic, Business, Management and Accounting Journal, 2025)
The tourism sector has a strategic role in regional economic development. Central Java, with its wealth of natural, cultural, and historical tourism, has great potential to develop the tourism sector as an economic driver. The development of supporting facilities such as hotels and restaurants, as well as an increase in tourist attraction, is expected to encourage the growth of GRDP in regencies/cities in Central Java.  This study examines the influence of the tourism sector on Gross Regional Domestic Product (GRDP) in 35 regencies and cities in Central Java. Using panel data from 2016 to 2022, this study evaluates how the number of hotels, restaurants, tourist attractions, and population affect GRDP. This study uses dynamic panel data regression method with Seemingly Unrelated Regression (SUR) approach. The results show that the number of hotels significantly increases GRDP, while the number of restaurants also has a positive and significant impact. In addition, tourism attraction provides a good contribution to GDRP, and the number of population provides a significant positive influence on GDRP throughout the Central Java region.